Technical report: approximate solution of linear homogeneous singular perturbation problem of second order ordinary differential equation using Differential Transform Method (DTM) / Nurzawani Mohamad Zamri - Mohamad Zamri, Nurzawani (2017)
In this research, a reliable algorithm is presented to develop an approximate solution of second order singular perturbation in which the highest order derivative is multiply with the small parameter, epsilon. In this method, the given problem and its boundary are transformed based on the table of the fundamental theorem of DTM. Then, from the transformed equation, the recurrence relation will be obtained and the equation with this problem can be solved using DTM. The accuracy and efficiency of the method are proved by some illustration of examples and by comparing the results with the exact solution. The obtained result is showing that DTM method is easy and convenient and efficient to use.